Analisis Prakiraan Kebutuhan Energi Listrik di Kabupaten Kolaka Utara menggunakan Metode Dkl 3.2, Regresi Linear dan Software Leap - Nur Rahmadani; Mustarum Musaruddin; Muh. Nadzirin Anshari Nur; Hasmina Tari Mokui; St. Nawal Jaya; Achmad Nur Aliansyah (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
This paper analyses the estimation of electrical energy demand in the North Kolaka Regency for the next few years and also analyses the accuracy of the forecasts from the methods used. The forecast methods used are the DKL 3.2, linear regression methods, and LEAP software with a BAU (Base as Usual) scenario. According to the results of the forecast of electrical energy demand for the upcoming five years using the DKL 3.2 method, there are 192548.29 customers, 31120935.67 kWh of electrical energy consumed, and 236523.48 kVA of connected power, respectively. Using the linear regression method, there are 197753 customers, 22733920.50 kWh, and 235493.40 kVA while using LEAP software, there are 219831.60 customers, 15351429.26 kWh and 274379.50 kVA. While the results of the analysis of the accuracy of the forecast method based on the MAPE and MSE value for the number of customers and the predicted power connected are the DKL 3.2 method, while for the consumption of electrical energy using the linear regression method.